An Analysis on Country Girls Trilogy and Epilog in Edna O’brien’s Fiction: Exploring Taboo Themes in Edna O’Brien’s Country Girls Trilogy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Country Girls is a set of three by Irish creator Edna O'Brien. It comprises of three novels The Country Girls (1960), The Lonely Girl (1962), and Girls in Their Married Bliss (1964). The set of three was re-delivered in 1986 out of a solitary volume with a changed closure of Girls in Their Married Bliss and expansion of an epilog. The Country Girls, both the set of three and the novel, is frequently credited with ending quiet on sexual issues and social issues during a severe period in Ireland following World War II and was adjusted into a 1983 film. Every one of the three novels were prohibited by the Irish restriction board and confronted critical open scorn in Ireland.[1] O'Brien won the Kingsley Amis Award in 1962 for The Country Girls.